Amino-diol borate complexation for controlling transport phenomena of penetrant molecules into polymeric matrices. Issue 36 (20th August 2019) - Unthank, Matthew G.; Cameron, Colin; Wright, Anthony; Hughes, David; Alam, M. Ashraf; Probert, Michael R.
Abstract : A new type of epoxy-amine-borate (EAB) hybrid material is reported for control of penetrant solvent molecules into cross-linked polymer networks. Abstract : The development of new high performance materials, coatings, composites and adhesives relies on insight into the origin of material performance on a molecular level. This paper explores a new type of epoxy-amine-borate (EAB) hybrid material for control of penetrant solvent molecules into cross-linked thermoset polymer networks.